Eutrophication reduces seagrass contribution to coastal food webs - Lijun Cui; Zhijian Jiang; Xiaoping Huang; Qiming Chen; Yunchao Wu; Songlin Liu; Jinlong Li; Peter I. Macreadie (Ecosphere, 2021)
Abstract Food sources and food web structure in seagrass meadows are important determinants of ecosystem functions and services. However, there is little information on the effect of eutrophication on food source contributions and food web structure in seagrass meadows. Here we used stable isotopes of carbon and nitrogen (δ13C and δ15N) to investigate how do different levels of nutrient enrichment affect the diets of consumers and food web structure within tropical seagrass meadows. We found that the diet contributions of macroalgae (mean 24% ± 12% for fish, 21% ± 5% for invertebrates), particulate organic matter (mean 19% ± 12% for fish, 18% ± 8% for invertebrates), and sediment organic matter (mean 24% ± 13% for fish, 21% ± 8% for invertebrates) to fish and invertebrates were all higher in seagrass meadows with higher nutrient concentrations, while seagrass and epiphytes contributed more to consumers in seagrass meadows with lower nutrient concentrations. Meanwhile, higher nutrient concentrations decreased the trophic position (mean 2.6 ± 0.5 in high‐nutrient level, 3.4 ± 0.6 in low‐nutrients level) of consumers and food chain length (2.5 in high‐nutrient level, 2.9 in low‐nutrients level). Higher nutrient concentrations reduced the contribution of seagrass carbon to consumers through the grazing food chain, but enhanced the flow of macroalgal carbon to consumers through the grazing food chain. Overall, eutrophication modified the food web structure of seagrass meadows. We recommend that measures be taken to decrease nutrient input into seagrass ecosystems to maintain its important functions and services.